A Call to Action: An Open Letter From Global Health Professionals. Signed By Over 3000 Global Health Professionals - Global Health Professionals (Social Medicine Publication Group, 2023)
The world is alight with horror, grief, and rage. In the last 34 days, we witnessed the mass killing of civilians and numerous violations of international law. The October 7 Hamas-led attacks on Israel resulted in the deaths of 1400 Israelis. Since then, over 10,818 Palestinians have been killed in Gaza, and 175 Palestinians have been killed by Israeli forces in the West Bank. These events occurred in the context of the decades-long occupation of the Palestinian territories. This escalation of hatred and violence needs to stop. We can and must do better to uphold human rights, health, and wellbeing through coordinated, immediate actions. The clarion call of the global health movement is to act for humanity regardless of borders or identity. As global health professionals, we strive for health, human flourishing, equity, peace, justice, and the end of colonialism in all its manifestations. We also unequivocally condemn violence against Indigenous peoples globally.